A cost-effective and reliable measurement strategy for 3D printed parts by integrating low- and high-resolution measurement systems. (3rd October 2018) - Wang, Kai; Tsung, Fugee
ABSTRACT: Metrology data are crucial to quality control of three-dimensional (3D) printed parts. Low-cost measurement systems are often unreliable due to their low resolutions, whereas high-resolution measurement systems usually induce high measurement costs. To balance the measurement cost and accuracy, a new cost-effective and reliable measurement strategy is proposed in this article, which jointly uses two-resolution measurement systems. Specifically, only a small sample of base parts are measured by both the low- and high-resolution measurement systems in order to save costs. The measurement accuracy of most parts with only low-resolution metrology data is improved by effectively integrating high-resolution metrology data of the base parts. A Bayesian generative model parameterizes a part-independent bias and variance pattern of the low-resolution metrology data and facilitates a between-part data integration via an efficient Markov chain Monte Carlo sampling algorithm. This multi-part two-resolution metrology data integration highlights the novelty and contribution of this article compared with the existing one-part data integration methods in the literature. Finally, an intensive experimental study involving a laser scanner and a machine visual system has validated the effectiveness of our measurement strategy in acquisition of reliable metrology data of 3D printed parts.